The relationship between self-interest and common good in Hobbes’s philosophy - Fodor, Tímea (Acta Cultura et Paedagogicae, 2026)
As we have seen, Hobbes argues that violating a contract cannot in any way serve selfinterest. While there may occasionally be exceptional situations in which desertion produces positive results, these are always the result of chance. Therefore, only adherence to the terms of the contract can legitimately support the pursuit of selfinterest. Moreover, it is not only in the interest of the individual, but also in the interest of the political community as a whole, that as few people as possible should desert, for this is the greatest form of peace and security. In this sense, if we accept the selfinterest-oriented anthropological characteristics and Hobbes’s perspective on circumstances, the theory of justice in Leviathan seems well-founded. According to this theory, a just act is one that is carried out in the light of adherence to the contract, while any other manifestation constitutes an injustice to oneself and others. Moreover, the injustice committed against oneself can certainly not serve anyone’s self-interest. The relevance of the charge of psychological egoism to Hobbesian concepts remains an open question, as does the practicality of implementing Hobbes’s theory. However, we can argue that in Hobbes’s conception, self-interest and the common good are intertwined and do not contradict the morality that arises from the creation of laws. Rather, they all point towards a single goal: the maintenance of peace and security in which the life of the individual is protected.